Impact of anthropogenic activity on water quality of Tasik Biru at Bukit Ibam, Muadzam Shah - Malini, Raja (2014)
The anthropogeflic activity is the impact of deterioration of current water quality status of Tasik Biru at Bukit Ibam, Muadzam Shah. Entirely, five sampling stations were selected within the study area in order to determine the current water quality characteristics. Both in-situ and ex-situ testing were conducted within the study area to test the selected parameters. From the experiment conducted, the average value of temperature and pH was 28.97°C and 8.19 respectively. Meanwhile, dissolved oxygen, chemical oxygen demand and biochemical oxygen demand recorded the average amount of 7.03 mg/L, 12.41 mg/L and 6.0 mgIL respectively. The study water was in class I for parameters such as nitrate and iron based on National Water Quality Standard (NWQS),. Additionally, turbidity and chemical oxygen demand was classified in class hA whereas pH, phosphate and dissolved oxygen was categorized in class JIB in accordance with NWQS. The temperature was within normal ranges under class III, electrical conductivity, total dissolved solids and biochemical oxygen demand parameters came under class IV according to NWQS. According to DOE-WQI of Malaysia, the water sample collected from January to March was classified as class III, which ranging from 64-.20 to 73.63. The water in this class indicated that intensive water treatment is necessary for tolerant aquatic life. For seasonal basis, the study water also classified in class III with the range of 64.20 up to 69.94. This result showed that the wet season was polluted than dry season. Both the anthropogenic activities have affected the water quality status of the lake. Based on study, the mining activity that was carried out in the past has increased the total dissolved solids and heavy metals constituents. As the overall, this study water is moderately polluted. Thus, the water can be used for public water supply after treatment besides, was suitable for navigation uses and treated water transportation as well.